Site preparation for the new Hong Kong international airport - Plant, G. W.; Covil, C. S.; Hughes, R. A. (Thomas Telford, 1998)
Edited and written by the engineers intimately involved in the project, this text presents both theory and practice in site reclamation and provides valuable lessons in site investigation geotechnical instrumentation and more.